Integrating Mixed Method Data in Psychological Research: Combining Q Methodology and Questionnaires in a Study Investigating Cultural and Psychological Influences on Adolescent Sexual Behavior. (October 2013) - Franz, Anke; Worrell, Marcia; Vögele, Claus
In recent years, combining quantitative and qualitative research methods in the same study has become increasingly acceptable in both applied and academic psychological research. However, a difficulty for many mixed methods researchers is how to integrate findings consistently. The value of using a coherent framework throughout the research process is discussed and arguments illustrated by referring to a study on individual- and cultural-level influences on sexual health behaviors conducted with adolescents in Germany and England. The article concludes that using an appropriate framework throughout the research process can ensure integration of findings in a consistent and coherent way. This can improve mixed methods research and produce greater "yield."